Metaspace as a megatrend: new horizons of retail transformation - Chernov, Oleksandr Oleksandrovich; Kyzliuk, Oleksandr Anatoliyovych (Східноєвропейський центр наукових досліджень, 2025)
This paper examines the impact of the megatrend of metaspace formation on the transformation of domestic retail in a turbulent environment. An analysis of statistical data, scientific sources and dynamic trends reveals that traditional consumer interaction models are no longer applicable to retail development. As a synthesis of physical, digital and virtual environments, meta-space establishes new vectors for retailer behaviour, encouraging deep digitalisation, flexible business models and new presence formats. The paper demonstrates that adapting to this megatrend is essential for Ukrainian retailers to remain competitive in the near future.
Keywords: retail; megatrend; meta-space; development; transformation